Lemah Abang Railway Crew Payroll Application Program at PT. X - Wahyu Eko Saputro (Journal of Business Social and Technology, 2021)
In today's modern era the world of technology and information is growing so rapidly, computers have become a very basic need and able to help all oprasional activities in all fields, therefore it takes a creativity to facilitate and ease daily work. This research aims to facilitate the process of collecting the salaries of THB ka crew in accordance with its service, to help reduce errors in the payment of official money to the ka crew in charge, in order to improve the performance of the Ka Crew in accordance with applicable official regulations, make an ease in the unit of Crew KA THB in the process of data processing, as well as as a positive input in determining a policy, producing programs that support the work of related units. The method used in this research is data collection method such as interview, observation and literature study. The results of research on the Lemah Abang Railway Crew Payroll Application program at PT. The Desktop-Based Indonesian Railway (Persero) is expected to report and pay more easily, precisely, and efficiently.